Investigating vibration characteristics of magnetostrictive transducers for air-coupled ultrasonic NDT of composites - Derusova D. A. Dariya Aleksandrovna; Vavilov V. P. Vladimir Platonovich; Kolomeets N. P.; Chulkov A. O. Arseniy Olegovich; Rubtsov V. E. Valery Evgenjevich; Kolubaev Е. А. Evgeny Aleksandrovich (2019, 2019)
Title screen